2017
DOI: 10.1097/md.0000000000006018
|View full text |Cite
|
Sign up to set email alerts
|

Seizure syndrome as a first manifestation of solitary tumor-like mass lesion of PACNS

Abstract: Rationale:Primary angiitis of the central nervous system (PACNS) is an inflammatory disease involving cerebrovascular and parenchymal, and solitary tumor-like mass lesion of PACNS (TLML-PACNS) is frequently misdiagnosed as neoplastic or other inflammatory diseases. However, seizure syndrome as a first manifestation of TLML-PACNS has rarely reported before.Patient concerns:Here, we report 2 cases of seizure syndrome, which was the first sign that presented prior to the diagnosis of TLML-PACNS by brain biopsy.Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…PACNS imaging methods can be divided into three categories based on the structures examined (16), of which MRI is the most common choice in practice (17). MRI findings of PACNS are sensitive but non-specific, and several studies have reported an MRI sensitivity ~90–100% (7, 14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PACNS imaging methods can be divided into three categories based on the structures examined (16), of which MRI is the most common choice in practice (17). MRI findings of PACNS are sensitive but non-specific, and several studies have reported an MRI sensitivity ~90–100% (7, 14).…”
Section: Discussionmentioning
confidence: 99%
“…The solitary tumor-like mass lesions of PACNS are rare, which usually show high signal intensity on T2 and heterogeneously enhancing signals on Gd-enhanced images (17, 2226). Previously reported mass-forming PACNS cases in adults from 2000 to the present are summarized in the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases were misdiagnosed as a brain tumor or an intracranial infection. Brain biopsy is the gold standard diagnostic modality, and cerebral angiography has low diagnostic power [34]. Magnetic resonance imaging is the preferred imaging in some hospitals, which shows single stenotic lesions in multiple blood vessels [35].…”
Section: Primary Central Nervous System Angiitismentioning
confidence: 99%
“…Also, there are no studies that prefer one immunosuppressive agent over others. One study showed good outcomes of using steroids and cyclophosphamide [34].…”
Section: Primary Central Nervous System Angiitismentioning
confidence: 99%
“…An underrecognized and rarer subset of PCNSV, approximately 5%-29%, can present with "masslike" or "tumefactive" lesions mimicking a neoplasm. 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To date, imaging features of tumefactive PCNSV (t-PCNSV) have not been well described and definitive diagnosis can only be made confidently on histopathology. [5][6][7][8][9][10] In this article, we performed a retrospective review of 10 histopathologically proved cases of t-PCNSV and analyzed pertinent imaging features with histopathologic correlation.…”
mentioning
confidence: 99%